2020
DOI: 10.1371/journal.pone.0235411
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with treatment initiation delay among new adult pulmonary tuberculosis patients in Tigray, Northern Ethiopia

Abstract: Background Delayed treatment initiation of Tuberculosis patients results in increased infectivity, poor treatment outcome, and increased mortality. However, there is a paucity of evidence on the delay in new adult pulmonary Tuberculosis patients to initiate treatment in Tigray, Northern Ethiopia. Objective To assess the factors associated with treatment initiation delay among new adult pulmonary tuberculosis patients in Tigray, Northern Ethiopia. Methods The study design was cross-sectional. A total of 875 new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The findings of this study also revealed that level of information about tuberculosis and educational status were strongly associated with treatment seeking delay. Other studies conducted in Ethiopia reported lower educational level as an independent predictor of treatment seeking delay [29,47]. Patients who had poor information about TB were more likely to have longer patients delay than those who had good information about TB [57].…”
Section: Plos Onementioning
confidence: 90%
See 2 more Smart Citations
“…The findings of this study also revealed that level of information about tuberculosis and educational status were strongly associated with treatment seeking delay. Other studies conducted in Ethiopia reported lower educational level as an independent predictor of treatment seeking delay [29,47]. Patients who had poor information about TB were more likely to have longer patients delay than those who had good information about TB [57].…”
Section: Plos Onementioning
confidence: 90%
“…All of the included studies were cross-sectional studies. The sample size ranged from 1700 [25] to 875 [29]. The studies were conducted between 2013 and 2020 across the country.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore BALF levels of sCD14, IL-17 and IL-22 may be used as triage biomarkers to not only refer patients with low levels to conduct lung biopsy, but also refer patients with moderate BALF levels to start anti-TB therapy immediately. Delays in treatment initiation may lead to worse clinical outcomes and increased transmission [32,33]. Empiric antibacterial therapy was the major cause of anti-TB delay in this study.…”
Section: Discussionmentioning
confidence: 76%
“…The data for each of the five associated factors were exported to Stata SE version 14 after extracting data on excel spreadsheet. Ten studies (7,9,10,35,(48)(49)(50)(51)(52)(53) assessed associated factors including patients socio-demographic characteristics, clinical characteristics, and diagnostic modalities. Six studies analyzed the relationship between sex and health system delay; four studies assess distance to the health facility with health system delay.…”
Section: Factors Associated With Health System Delaymentioning
confidence: 99%